Bacteriophage Isolation, Purification, and Characterization Techniques Against Ubiquitous Opportunistic Pathogens. Issue 11 (16th November 2022) - Peters, Danielle L.; Harris, Greg; Davis, Carly M.; Dennis, Jonathan J.; Chen, Wangxue
Abstract: Healthcare‐associated infection with "ESKAPE" pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) is a global health crisis due to their extensive intrinsic antibiotic resistance and the ability to quickly acquire resistance determinants. Alternative treatment options are required to combat this crisis, and one possibility is the use of bacteriophages, or viruses that strictly infect the pathogenic bacteria. Currently, there is a renaissance in research and development into the use of phages to target multi‐, extensively, and pan‐resistant bacterial infections in humans, known as phage therapy. Using A. baumannii as an example, this article describes the isolation and purification of bacteriophages from sewage and soil samples, as well as general methods used in phage research such as precipitation of phages using polyethylene glycol, host range analysis, single‐cell burst size determination, DNA extraction, and restriction fragment length polymorphism analysis. © 2022 National Research Council Canada. Current Protocols © 2022 Wiley Periodicals LLC. Reproduced with the permission of the Minister of Innovation, Science, and Industry. Basic Protocol 1 : Isolation of bacteriophages against A. baumannii from sewage samples Alternate Protocol 1 : Isolation of bacteriophages against A. baumannii from soil samples Support Protocol 1 : Titering a bacteriophage stock Basic Protocol 2 : Purification of phage to an axenic working stock Support Protocol 2 : Liquid propagation of bacteriophage Basic Protocol 3 : Host range analysis using the spot plate method Basic Protocol 4 : Single burst size analysis Alternate Protocol 2 : One‐step growth curve Basic Protocol 5 : Precipitation of bacteriophage using PEG 6000 Basic Protocol 6 : DNA extraction from dsDNA bacteriophages Basic Protocol 7 : Restriction fragment length polymorphism analysis of novel phage genomes